New strategies for identifying and masking the bitter taste in traditional herbal medicines: The example of Huanglian Jiedu Decoction - Ke, Xiumei; Ma, Hongyan; Yang, Junxuan; Qiu, Min; Wang, Jianwei; Han, Li; Zhang, Dingkun (Frontiers in Pharmacology, 2022)
It is difficult to suppress the bitter taste of traditional Chinese medicine (TCM) largely due to its complex ingredients, unknown material basis of bitter substances, and high dispersion of bitter ingredients in the liquid preparation. And we developed a novel strategy for identifying bitter ingredients, masking the bitter taste, and elucidated the mechanism of flavor masking in TCM. And HuangLian Jie-Du decoction (HLJDD), with a very intense bitter taste, was studied as a typical case. Firstly, the chemical components in HLJDD were analyzed using UPLC-MS/MS, whereas the bitter substances were identified by pharmacophore. In addition, the screening results of the pharmacophore were further validated using experimental assays. The mask formula of HLJDD was effectively screened under the condition of clear bitter substances. Computational chemistry, molecular docking, and infrared characterization (IR) techniques were then used to elucidate the mechanism of flavor masking. It was found that neotame, γ-CD, and mPEG2000-PLLA2000 significantly reduced bitterness of HLJDD. Specifically, mPEG2000-PLLA2000 increased the colloid proportion in the decoction system and reduced the distribution of bitter components in the real solution. Sweetener neotame hampered bitter taste perception and inhibited bitter taste receptors activation to reduce bitter taste. The γ-CD included in the decoction bound the hydrophobic groups of the bitter ingredients in real solutions, and “packed” all or part of the bitter ingredients into the "cavity". This study established a novel strategy for screening bitter substances in TCM through combining virtual screening and experimental assays. Based on this strategy, the taste mask of TCM was carried out from three different perspectives: changing the drug phase state, component distribution, and interfering with bitter signal transduction. Collectively, the methods achieved a significant effect on bitter taste suppression and taste masking. The findings will provide a new strategy for masking the taste of TCM liquid preparation/decoction, which will help in improving the clinical efficacy of TCM.